KAJIAN MANAJEMEN MUTU DALAM PENCAPAIAN RENDEMEN CPO (CRUDE PALM OIL) ( STUDI KASUS : PT. BAKRIE SUMATERA PLANTATION TBK KISARAN PALM OIL MILL ) - Ningsih, Tuty; Ishman L Sibuea; M. Siddiq Dongoran (Jurnal Agro Fabrica, 2020)
The achievement of oil Extraction Rate is one of the palm oil mill performances that needs to be continuouslyimproved. The achievement of oil Extraction Rate is obtained from efforts to synergize plant parts andprocessing plants which must be managed with a good management system. The implementation of anappropriate and consistent quality management system (Plan, do, check, action/PDCA) is expected toincrease optimal yield in accordance with predetermined targets. This research method is descriptivequantitative with research variables processing capacity, production yield, production quality and processingcosts. The results showed that (1) The company's management efforts in achieving CPO yield are integratingonfarm and off farm that are managed by implementing a quality managemen System (Plan, do, Check,Action/PDCA). (2) The Relationship of the ISO 9001;2015 to that affect the yield of CPO : (a) Planned 23,5% oil yield by 2020, (b) Establish and implement SOP and IK in onfarm and off farm. (c) Performs externaland Internal audits every years.